External Modifications of Requests among Jordanian University Students: A Socio-Pragmatic Analysis - Al-Rousan, Mohammad; Alsharairi, Rania Abd Alhameed (Journal of Ecohumanism, 2024)
The primary purpose of this study is to explore the external modifications of requests among Jordanian male and female university students in cross-gender settings and the factors affecting the choice of these strategies. The subjects of the study were 18 Jordanian undergraduate university students (9 males and 9 females) enrolled in different programs at Ajloun National University, Jordan. A mixed methodological approach was adopted for data collection. The data was retrieved from nine-hour audio recordings to gather naturally-occurring data and 18 DCTs to elicit organized data sets that can be analyzed based on patterns. Blum-Kulka et al.’s (1989) taxonomy of request strategies was espoused to analyze the obtained data. The data analysis revealed that the mitigating supportive moves (i.e., Imposition Minimizers, grounders, disarmers, preparators, getting a pre-commitment, promise of reward) were preferred by female students more than their male counterparts, whereas male students used Aggravating supportive moves (i.e., Threat, insult, Moralizing) more frequently than female students. Interestingly, other unique features that can be subsumed under Mitigating supportive moves manifested in Jordanian students’ requests, Namely, apology, self-introduction and gratitude. It was concluded that request strategies are not only used to fulfill certain needs, but also to manage social interactions and to strengthen relationships. Moreover, the way in which Jordanians use request strategies is strongly influenced by gender, cultural norms, and the context of interaction.